2023
DOI: 10.1186/s13213-022-01703-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell phenotype changes and oxidative stress response in Vibrio spp. induced into viable but non-culturable (VBNC) state

Abstract: Purpose Aquatic bacteria of the genus Vibrio include animal and human pathogens. The occurrence of Vibrio-related diseases has been associated with the current climate change-driven increase of sea surface temperature. Vibrio spp. can enter into the viable but non-culturable (VBNC) state, as a consequence of starvation in seawater at low temperatures. In such physiological state, Vibrio cells are no longer culturable on standard media agar plates but can resuscitate if incubated at 30 °C prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The results showed that the reactive oxygen content of brewer's yeast increased during the formation of the VBNC state, which was positively correlated with the number of VBNC cells. This is consistent with Prosdocimi's suggestion that the formation of Vibrio vulnificus in the VBNC state is related to oxidative stress [29] .…”
Section: Changes In Ros Content During the Vbnc Yeast Formationsupporting
confidence: 92%
“…The results showed that the reactive oxygen content of brewer's yeast increased during the formation of the VBNC state, which was positively correlated with the number of VBNC cells. This is consistent with Prosdocimi's suggestion that the formation of Vibrio vulnificus in the VBNC state is related to oxidative stress [29] .…”
Section: Changes In Ros Content During the Vbnc Yeast Formationsupporting
confidence: 92%